APPLICATION OF FOURIER TRANSFORM INFRARED SPECTROSCOPY (FTIR) IN SAMPLE PREPARATION: MATERIAL CHARACTERIZATION AND MECHANISM INVESTIGATION - Fitriah, Nurul (Jurnal Sains dan Teknologi Reaksi, 2025)
Fourier Transform Infrared Spectroscopy (FTIR) is an instrumental analysis technique that is widely used in the fields of materials science, engineering, and microbiology. The principle of FTIR is based on molecular vibrations that produce a characteristic spectrum as a “molecular fingerprint.” In sample preparation, FTIR plays an important role in material characterization (solid sorbents, metal organic frameworks, hybrid materials) and investigation of the extraction mechanisms of organic, inorganic, and biomacromolecular molecules. This study used a quantitative descriptive approach with observation, interviews, and documentation at the Analytical Chemistry Laboratory of the Lhokseumawe State Polytechnic. The results show that FTIR is most effective in the field of materials science (85%), followed by microbiology and the environment (80%), and least effective in asphalt and materials engineering (75%). With its speed, non-destructive nature, and flexibility, FTIR has great potential, although the interpretation of complex spectra remains a major challenge. Keywords: FTIR, material characterization, sample preparation, extraction mechanism, bioremediation